Գևորգ Դևրիկյանի «Գոյամարտ» վեպը - Երկանյան, Աննա
В данной статье исследуется идейно-художественный аспект романа армянского советского писателя Геворга Деврикяна „Борение” (1986г.), в центре которого столица Ани, стоящая на грани уничтожения. Дается соответсвие романа и историческому окружению и постижению времени, и актуальности. Анализируется образ неопытного царя Гагика, не остаются без внимания и другие герои: Сенекерим Арцруни, Ваграм Пахлавуни. В статье представлена главная идея романа „Борение”, раскрывается тайна выживания армянского народа. In this article we are going to present the novel “Battle” by the Soviet Union writer Gevorg Devrikyan, which investigates the city of Ani, which was at the edge of distruction , in an artistic sence. It shows the novel’s match both with the time of the historical environment and perceptions and also with modernity. In this novel , the writer analyzes the character of inexperienced King Gagik, and also refers to the novel’s other characters. Senekerim Artsruni, Vahram Pahlavuni. In this article it is presented the main idea of the novel “Battle” and also it clarifies the secret of permanence of Armenian people.
Keywords: Գրականագիտություն